Inhibiting MARCH5/Mfn2 signaling as an alternative strategy to protect cardiomyocytes from hypoxia-induced mitochondrial dysfunction - Faten Habrat Zoabi; Mulate Zerihun; Roy Lizarovich; Chiara Dalla Torre; Liron Davis; Offir Ertracht; Michal Barsheshet; Shaul Atar; Deborah E. Shalev; Marta De Zotti; Hanoch Senderowitz; Nir Qvit (Computational and Structural Biotechnology Journal)
The mitochondrial E3 ubiquitin ligase membrane-associated RING-CH-type finger 5 (MARCH5) and the GTPase Mitofusin 2 (Mfn2) both play crucial roles in regulating mitochondrial dynamics, which are essential for cellular homeostasis. Dysregulation of the MARCH5/Mfn2 signaling has been implicated in mitochondrial dysfunction, a key factor in cardiovascular diseases (CVDs). To investigate the therapeutic potential of targeting this interaction, we developed a novel peptide, CVP-220, designed to specifically disrupt the MARCH5/Mfn2 protein interaction. Using a hypoxia-reoxygenation (H/R) injury model in rat cardiomyocyte cell lines, CVP-220 demonstrated significant cardioprotective effects. Treatment with CVP-220 enhanced cell viability by 30 % compared to untreated controls and reduced reactive oxygen species (ROS) production by 45 %, suggesting improved mitochondrial function. Notably, CVP-220 selectively modulated MARCH5-mediated ubiquitination of Mfn2 without affecting other MARCH5 interactions, thereby preserving mitochondrial fusion and preventing fragmentation under stress conditions. A plausible binding mode of CVP-220 on Mfn2 was suggested through a combination of molecular docking and molecular dynamics simulations and was experimentally validated by mutational analysis. These findings highlight CVP-220 as a promising tool for modulating mitochondrial dynamics and mitigating mitochondrial damage in cardiac cells, with potential implications for therapeutic strategies targeting mitochondrial dysfunction in CVDs. Further investigation into the role of MARCH5/Mfn2 signaling in cardiac pathology could pave the way for novel peptide-based treatments.